Можливості венчурного фінансування в умовах інтеграції України до європейського інноваційного простору - Лях, І.І. (Вісник економічної науки України, 2020)
Стаття присвячена проблематиці інтеграції України до інноваційного простору Європейського Союзу, особлива роль в якої належить венчурному бізнесу, що відрізняється від інших форм реалізації інновацій за методами мобілізації капіталу, структурою джерел і умовами залучення інвестицій, а також використанням нових фінансових інструментів.
Аргументовано, що темпи зближення України з ЄС за інноваційним напрямком не є задовільними: є певні позитивні зрушення, але виявлено чимало проблем, зокрема, з венчурним фінансуванням інноваційної діяльності. Аналіз венчурних угод компаній з управління активами серед інститутів спільного інвестування (ІСІ) доводить: венчурні фонди практично не вкладають кошти у високотехнологічні галузі, за виключенням деяких напрямів фінансових послуг та ІКТ. Найпоширеніші випадки надання фінансової підтримки з боку венчурного капіталу в Україні стосуються таких видів економічної діяльності, як: будівництво, торгівля, готельний і туристичний бізнес, переробка сільгосппродукції, страхування, видавнича діяльність.
Протягом останніх років спостерігається тенденція помірного та екстенсивного росту українського
сектору управління активами, переважно за рахунок активності нових фондів. Розвиток венчурних інвестиційних фондів в Україні фокусується у регіонах-лідерах за вкладом в економічний розвиток країни. Як і раніше, відбувається зростання рівня концентрації фондів венчурного бізнесу переважно в столиці та Київській області.
У статті обґрунтовано необхідність та запропоновано заходи щодо подолання регіональної асиметрії в наданні фінансових послуг ІСІ, що базуються на посиленні взаємодії між інститутами спільного інвестування, з одного боку, та інвесторами й емітентами цінних паперів, з іншого боку, що сприятиме забезпеченню ефективності інвестування та зниженню пов’я¬заних з цим процесом трансакційних витрат. Для цього важливим є створення відповідної екосистеми інноваційного інвестування, яка забезпечить доступ до фінансових послуг, що надаються ІСІ, всім потенційним інвесторам на ринку цінних паперів (громадянам та бізнес-спільноті країни) незалежно від регіональної приналежності. Статья посвящена проблематике интеграции Украины в инновационное пространство Европейского Союза, особая роль в которой принадлежит венчурному бизнесу, который отличается от других форм реализации инноваций методами мобилизации капитала, структурой источников и условиями привлечения инвестиций, а также использованием новых финансовых инструментов.
Аргументировано, что темпы сближения Украины с ЕС по инновационному направлению не являются удовлетворительными: есть определенные положительные сдвиги, но выявлено немало проблем, в частности, с венчурным финансированием инновационной деятельности. Анализ венчурных сделок компаний по управлению активами среди институтов совместного инвестирования (ИСИ) доказывает: венчурные фонды практически не вкладывают средства в высокотехнологичные отрасли, за исключением некоторых направлений финансовых услуг и ИКТ. Самые распространенные случаи предоставления финансовой поддержки со стороны венчурного капитала в Украине касаются таких видов экономической деятельности, как: строительство, торговля, гостиничный и туристический бизнес, переработка сельхозпродукции, страхование, издательская деятельность.
В последние годы наблюдается тенденция умеренного и экстенсивного роста украинского сектора управления активами, преимущественно за счет активности новых фондов. Развитие венчурных инвестиционных фондов в Украине сосредоточено в регионах-лидерах по вкладу в экономическое развитие страны. Как и раньше, происходит повышение концентрации фондов венчурного бизнеса преимущественно в столице и Киевской области.
В статье обоснована необходимость и предложены меры по преодолению региональной асимметрии в предоставлении финансовых услуг ИСИ, основанные на усилении взаимодействия между институтами совместного инвестирования, с одной стороны, и инвесторами и эмитентами ценных бумаг, с другой стороны, что будет способствовать обеспечению эффективности инвестирования и снижению связанных с этим процессом трансакционных издержек. Для этого важным является создание соответствующей экосистемы инновационного инвестирования, которая обеспечит доступ к финансовым услугам ИСИ, всем потенциальным инвесторам на рынке ценных бумаг (гражданам и бизнес-сообществу страны) независимо от региональной принадлежности. The paper is devoted to the issue of Ukraine's integration into the innovation space of the European Union, in which a special role belongs to venture business, which differs from other forms of innovation in terms of capital mobilization, source structure and investment conditions, as well as the use of new financial instruments.
It is argued that the pace of Ukraine's approaching with the EU in the field of innovation is not satisfactory: there are some positive changes, but many problems have been identified, in particular with venture financing of innovation. An analysis of venture agreements of asset management companies among mutual investment institutions (MIIs) shows that venture funds do not invest in high-tech industries, with the exception of some branches of financial services and ICT. The most common cases of financial support from venture capital in Ukraine relate to such economic activities as: construction, trade, hotel and tourism business, processing of agricultural products, insurance, publishing.
In recent years, there has been a trend of moderate and extensive growth in the Ukrainian asset management sector, mainly due to the activity of new funds. The development of venture capital funds in Ukraine concentrates on the leading regions in measuring their contribution to the country's economic development. As before, the level of concentration of venture business funds is growing, mainly in the capital and Kyiv region.
The paper substantiates the need and proposes measures to overcome the regional asymmetry in the provision of MIIs financial services, based on strengthening the interaction between mutual investment institutions, on the one hand, and investors and issuers of securities, on the other hand. These measures will help ensure investment efficiency and reduce transaction costs related to this process. To this end, it is important to create an appropriate ecosystem of innovative investment, which will provide access to financial services provided by MIIs to all potential investors in the securities market (citizens and the business community of the country), regardless of regional affiliation.
In recent years, there has been a trend of moderate and extensive growth in the Ukrainian asset management industry, mainly due to the activity of new funds. The development of venture investment funds in Ukraine focuses on the leading regions in terms of contribution to the country's economic development. As before, the level of concentration of venture industry funds is growing, mainly in the capital and Kyiv region. The article substantiates the need and proposes measures to overcome the regional asymmetry in the provision of CII financial services, based on strengthening the interaction between mutual investment institutions, on the one hand, and investors and issuers of securities, on the other hand, which will help ensure investment efficiency and reduce related to this process transaction costs. To this end, it is important to create an appropriate ecosystem of innovative investment, which will provide access to financial services provided by CII to all potential investors in the securities market (citizens and the business community of the country), regardless of regional affiliation.